Investigation of cold-resistance mechanisms in cryophylactic yeast Metschnikowia pulcherrima based on comparative transcriptome analysis - Yuan, Zaizhu; Ge, Zhengkai; Fu, Qingquan; Wang, Fangfang; Wang, Qingling; Shi, Xuewei; Wang, Bin (Frontiers in Microbiology, 2024)
Low temperature inhibits the growth of most microorganisms. However, some microbes can grow well in a low temperature, even a freezing temperature. In this study, the mechanisms conferring cold resistance in the cryophylactic yeast Metschnikowia (M.) pulcherrima MS612, an isolate of the epidermis of ice grapes, were investigated based on comparative transcriptome analysis.Results showed that a total of 6018 genes and 374 differentially expressed genes (> 2-fold, P < 0.05) were identified using RNA-Seq. The differentially expressed genes were mainly involved in carbohydrate and energy metabolism, transport mechanisms, antifreeze protection, lipid synthesis, and signal transduction. M. pulcherrima MS612 maintained normal growth at low temperature (5℃) by enhancing energy metabolism, sterol synthesis, metal ion homeostasis, amino acid and MDR transport, while increased synthesis of glycerol and proline transport to improve its resistance to the freezing temperature (-5℃). Furthermore, cAMP-PKA and ERAD signaling pathways contribute to resist the low temperature and the freezing temperature, respectively.This study provides new insights into cold resistance in cryophylactic microorganisms for maneuvering various metabolism to resist different cold environment.